SYNTHESIS OF POLY(ASPARTATE-ASPARAGINE) GRAFT COPOLYMER AS CORROSION INHIBITOR AND SCALE INHIBITOR ON CARBON STEEL - Rangga Brata Sena, Muhammad
Corrosion and scale fonnation are problems that are always found on the inner surfaces of fluid flow pipes in various industries. The effects caused by corrosion include the occurrence of a pipe leak. and scale can reduce the tluid tlow rate. This results in environmental pollution and material losses. To overcome the corrosion and the exposure to the inner surface of the pipe, the addition of corrosion and scale inhibitors into the tluid flow is done. In its development, polyaspartate is used as a corrosion and scale inhibitor because it has large solubility in water, is biodegradable, and is also able to be a chelating compound. In this study. the synthesis of polysucinimide compounds as intennediate compounds is carried out and continued by the copolymerization reaction between polysuccinimide and L-asparagine to produce poly(aspartate-asparagine) compou nds (PASPA) to increase the efficiency of inhibition of corrosion and the exposure of polyaspartate. Characterization of PASPA compounds is carried out using Fourier Transform Infrared (FTIR) and Nuclear Magnetic Resonance (NMR) spectroscopy. Furthermore, the anal ysis of corrosion inhibition efficiency is carried out using the method of Electrochemical Impedance Spectroscopy (EIS). Tafel Polarization. and Weight loss measurement. In addition. the analysis of scal e inhibition efficiency is carried out by applying complexometry method using EDTA. FTIR characterization of PASPA shows a typical peak in the range of 2800-3900 em•' which indicates a new bond that is N-H vibration. NMR characterization shows a peak around 2.64 -2.91 ppm of the methylene proton and peaks around 3.61 - 3.92 ppm of the methine proton. Characterization resu lts show that PASPA compounds have been successfully synthesized. Anal ysis of the efficiency of corrosi on inhibition of PASPA in I% NaCI solution shows results that are quite effective at 45 oc at 46.83% and classified as mixed inhibitors. PASPA testing as a scale inhibitor showed very effective efficiency at 50 ppm concentration more than 99%. These results indicate that PASPA is an effective inhibitor to reduce corrosion rate in carbon steel in I% NaCI environment and formation ofCaCO, crystals (sca le).